2020
DOI: 10.5505/tjo.2019.1845
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/Lymphocyte Ratio and Prognosis in Patients with Non-Metastatic Nasopharyngeal Cancer: A Single-Center Experience

Abstract: Nasopharyngeal cancer's presentation and prognosis are variable. Even patients with the same clinical stage can have very different prognoses. The aim of the present study was to investigate clinical outcomes and prognosis, especially the effects of neutrophil/lymphocyte ratio (NLR), of non-metastatic nasopharyngeal carcinoma (NPC) in patients receiving radiotherapy (RT)±chemotherapy (CT) between March 2006 and August 2017 in the Eskişehir Osmangazi University Medical Faculty of Radiation Oncology Department. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Among the 64 studies on non-TNM factors, 18 proposed parameters were identified. Prognostic factors with consistent support from multiple studies included EBV-DNA level ( Table 3 ), primary gross tumor volume (GTV) ( 63 , 72 74 , 76 , 78 81 ), nodal GTV ( Table 4 ) ( 74 , 75 , 77 , 81 ), neutrophil-lymphocyte ratio (NLR) ( Table 5 ) ( 83 , 85 , 91 , 92 , 97 ), C-reactive protein (CRP)/albumin ratio ( 83 , 89 , 98 ), anemia ( 84 , 87 , 96 ), platelet count ( 82 , 86 ), lactate dehydrogenase (LDH) ( 88 , 95 ), and SUV max of the primary tumor ( 99 101 , 103 , 108 , 111 , 113 ) and total lesion glycolysis (TLG) ( Table 6 ) ( 104 , 111 ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Among the 64 studies on non-TNM factors, 18 proposed parameters were identified. Prognostic factors with consistent support from multiple studies included EBV-DNA level ( Table 3 ), primary gross tumor volume (GTV) ( 63 , 72 74 , 76 , 78 81 ), nodal GTV ( Table 4 ) ( 74 , 75 , 77 , 81 ), neutrophil-lymphocyte ratio (NLR) ( Table 5 ) ( 83 , 85 , 91 , 92 , 97 ), C-reactive protein (CRP)/albumin ratio ( 83 , 89 , 98 ), anemia ( 84 , 87 , 96 ), platelet count ( 82 , 86 ), lactate dehydrogenase (LDH) ( 88 , 95 ), and SUV max of the primary tumor ( 99 101 , 103 , 108 , 111 , 113 ) and total lesion glycolysis (TLG) ( Table 6 ) ( 104 , 111 ).…”
Section: Resultsmentioning
confidence: 87%
“…In the 18 studies that were included, nine inflammatory/hematological markers were evaluated: the most frequently proposed marker (n = 5) is NLR ( 83 , 85 , 91 , 92 , 97 ), followed by anemia (n = 3) ( 84 , 87 , 96 ), LDH (n = 2) ( 88 , 95 ), platelet count (n = 2) ( 82 , 86 ), and the CRP/albumin ratio (n = 3) ( 83 , 89 , 98 ). Other proposals with limited supporting evidence included high-sensitivity CRP (hs-CRP; n = 1) ( 54 ), platelet distribution width (PDW) ( 86 ), prognostic nutrition index (PNI) and albumin/globulin ratio (AGR) (n = 1) ( 93 ), D-dimer (n = 1) ( 94 ), and tumor-infiltrating lymphocytes (TIL; n = 1) ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows the characteristics of the 14 included studies 21,29–41 . All were performed between 2012 and 2021, with study populations ranging in size from 62 to 1550 patients.…”
Section: Resultsmentioning
confidence: 99%